Bible Didactics and Social Inequality? Critical Considerations on the Interconnection of Religious Education and Heterogeneous Settings - Winkler, Kathrin; Scholz, Stefan (Religions, 2022)
This paper deals with the question, to what extent, in the German context, have biblical didactic implications and systemic requirements in religious education led to social inequality in heterogeneous classrooms. Based on four different case studies in elementary, middle, and vocational schools, an empirical insight is provided that sheds exploratory and descriptive light on the construction of reality in the context of biblical learning. The analysis clearly shows that physical as well as socialization-related limitations, structural and systemic conditions in the German school system, and also strangeness and existential irrelevance, are obvious barriers that prevent students in heterogeneous settings from accessing biblical learning. In the synopsis, with theological-pedagogical implications as well as didactical challenges, it becomes clear how necessary difference-sensitive Bible didactics in the context of heterogeneity and social inequality is. Finally, based on the empirical evidence of the analyzed case studies and the theoretical framings, concrete expectations for biblical learning in religious education, in relation to heterogeneity and social inequality, are highlighted.
CRIS-Team WoS Importer:2022-06-10

Subaltern Thinking in Religious Education? Postcolonial Readings of (German) Schoolbooks - Winkler, Kathrin; Scholz, Stefan (British Journal of Religious Education, 2020)
This paper deals with the disclosure of subaltern thinking in current German-language textbooks for religious education. For the hermeneutical framing of this analysis, the approach of a postcolonial reading is particularly profitable. Obvious hierarchical relationships from clearly up and down can consequently be made visible and their presumed self-evidence unmasked. Even hidden hegemonic forms of expression can be uncovered in this way. With regard to current theology and religious education racism and misogyny, environmental degradation and sexual exploitation are attitudes that have already and almost as amatter of course been taken up critically. They are pedagogically reflected and attempted to overcome by using counter-models such as cultural diversity, equal rights, sustainability and sexual self-determination.In exciting contrast to this there are still nowadays textbooks used with remnants of exactly such formats of colonial thoughts. We argue that decolonising schoolbooks can be a useful part of decolonising the religious education curriculum. The schoolbook analysis carried out for this purpose is structured by four leading categories: Anthropological assumptions (1), religious classifications and interpretations (2), conceptions of culture and its hybridity (3) and finally the relationship to creation and environment (4). Textbooks from primary, secondary and vocational schools were examined.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Postcolonial Studies; religious Education; schoolbook Analysis; subaltern thinking